Thresholds in the relationship between functional diversity and patch size for mammals in the Brazilian Atlantic Forest - Magioli, M.; Ribeiro, M. C. [UNESP]; Ferraz, K. M. P. M. B.; Rodrigues, M. G. (Wiley-Blackwell, 2015)
Patch size affects abundance and diversity of mammal species, but there is little information on threshold regarding this relationship or relating it to functional diversity. Therefore, we aimed with this study to (1) evaluate if the functional diversity of medium-and large-sized mammal assemblages can be explained by patch size; (2) if this relationship is positive, evaluate whether it is linear (neutral hypothesis) or has critical thresholds (threshold hypothesis); (3) propose specific conservation strategies for each situation. We used primary and secondary mammal database for different forest remnants sizes in the Brazilian Atlantic Forest biome. We calculated functional diversity (FD), using an ecologically meaningful set of traits: body mass and locomotion form, behavioral and dietary traits, and environmental sensitivity of species. We compared linear models with threshold models using Akaike information criterion (AIC). FD values increased with patch size, possibly associated with the high complexity and heterogeneity of larger areas. The threshold model better explained the pattern between FD values and patch sizes than the linear one (delta AIC = 35.8), confirming our threshold hypothesis. Two thresholds (at 60 and 2050 ha) were identified. Our results highlight the need of compliance with the Brazilian Forest Code for assemblages in fragments lower than 60 ha. For assemblages in fragments between the two thresholds whose FD values significantly increased with patch size, we recommend improvements in conservation planning. For assemblages in fragments bigger than 2050 ha, we suggest the establishment of new protected areas, or at least, the maintenance of the existent ones. Our approach can serve as the basis for analysis with other taxonomic groups and ecosystems, increasing chances of maintaining faunal ecological functions, and improving species conservation.
Keywords: biodiversity; ecological functions; conservation planning; Brazil; patch size; mammal assemblages; fragmented habitat; functional diversity